Réalisation et Commande d’une machine CNC à 3 axes - Chouikh, Tahar; Chouiref, Badreddine; Delleabani, Hamza (université d'eloued, 2023)
"This project is a study, design and construction of a CNC machine. The objective of this work is to deepen knowledge in the fields of digital production. Following state-of-the-art CNC machines, this work is divided into three parts: one part includes electrical studies and mechanical studies and designs, the second part deals with numerical simulations and the last part deals with implementation, programming and commissioning. in service" "هذا المشروع عبارة عن دراسة وتصميم وبناء آلة .CNC الهدف من هذا العمل هو تعميق المعرفة في مجاالت اإلنتاج وفق ألحدث ماكينات CNC ، ينقسم هذا العمل إلى ثالثة أجزاء: الجزء األول يشمل الدراسات الكهربائية والدراسات ً الرقمي. ا والتصميمات الميكانيكية ، والجزء الثاني يتعامل مع المحاكاة العددية والجزء األخير يتناول التنفيذ والبرمجة والتشغيل. في الخدمة."
مذكرة ماستر الكتروميكانيكdes thèses électromécanique
Keywords: CNC machine, control, arduino; integrated circuit .; تحكم، أردوينو، دارة مدمجة، ماكنة التحكم الرقمي